Theorising media and practice - Bräuchler, Birgit; Postill, John (New York : Berghahn Books, 2010)
Introduction : theorising media and practice / John Postill ## Media as practice. Theorising media as practice / Nick Couldry ## What do we mean by 'media practices'? / Mark Hobart ## Media as practice: a brief exchange / Nick Couldry and Mark Hobart ## Media, culture and practice. From fan practice to mediated moments: the value of practice theory in the understanding of media audiences / S. Elizabeth Bird ## Thick context, deep epistemology: a meditation on wide-angle lenses on media, knowledge production and the concept of culture / Debra Spitulnik ## "But it is my Hhbit to read the Times": metaculture and practice in the reading of Indian newspapers / Mark A. Peterson ## Embedded/embedding media practices and cultural production / Ursula Rao ## Media practices in context. Communication, cognition and usage: epistemological considerations of media practices and processes / Guido Ipsen ## Language-games, in/dividuals and media uses: what a practice perspective should imply for media studies / Jo Helle-Valle ## A barthian approach to practice and media: Internet engagements among teleworkers in rural Denmark / Jens Kjaerulff ## Can practice theory inspire studies of ICTs in everyday life? / Toke H. Christensen and Inge Ripke ## New media production practices. Playful pactices: theorising 'new media' cultural production / Elisenda Ardèvol ... [et al.] ## Theorising the practices of free software: the movement / Christopher M. Kelty ## Cinematography and camera crew: practice, process and procedure / Cathy Greenhalgh.
Collection of papers, some of which were presented at a media anthropology network workshop, organised by the editors as part of the European Association of Social Anthropologists' (EASA) conference held in Bristol, U.K., September, 2006
Onderzoek KASK (1KA-OF1001)
boek